2013
DOI: 10.1038/bjc.2013.694
|View full text |Cite
|
Sign up to set email alerts
|

Increased microvascular proliferation is negatively correlated to tumour blood flow and is associated with unfavourable outcome in endometrial carcinomas

Abstract: Background:We aimed to study the angiogenic profile based on histomorphological markers in endometrial carcinomas in relation to imaging parameters obtained from preoperative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and diffusion-weighted imaging (DWI) and to explore the potential value of these markers to identify patients with poor outcome.Methods:In fifty-four surgically staged endometrial carcinoma patients, immunohistochemical staining with factor VIII and Ki67 allowed assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 27 publications
2
45
1
1
Order By: Relevance
“…This result was consistent with the previous study[7]. This differed from other studies: negative correlation between K trans and MVD[9] and no association [6,8,19] (Table5).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result was consistent with the previous study[7]. This differed from other studies: negative correlation between K trans and MVD[9] and no association [6,8,19] (Table5).…”
Section: Discussionsupporting
confidence: 92%
“…The only study regarding breast DCE MRI demonstrated positive correlation between K trans , k ep and MVD in benign and malignant profiles of breast disease[7]. Previous studies placed a region of interest (ROI) in a small area surrounding tumor periphery or on the largest area on a single axial scan[810] and small areas of high K trans values within the tumor[6]. These methods resulted in observer bias and insufficient information regarding tumor heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] They both increase with the microvascular blood flow, vascular permeability, and microvessel density of the internal microstructure of the diseased tissue. [33][34][35] In the current study, both K trans and K ep values showed no significant differences between ONBs and SCCs, probably because both tumors can disrupt vascular endothelial cells and result in increased vascular permeability and leakage of the contrast agent. In addition, iAUC 60 is associated with tumor blood influx, perfusion, and interstitium, representing the general tumor blood flow, overall perfusion, and tumor interstitial space index.…”
Section: Discussioncontrasting
confidence: 51%
“…K trans is a rate constant, qualifying the contrast agent diffusion from the blood plasma through the capillary wall into the EES, whereas K ep is a reverse rate constant of the contrast agent diffusion from the EES back to the plasma . They both increase with the microvascular blood flow, vascular permeability, and microvessel density of the internal microstructure of the diseased tissue . In the current study, both K trans and K ep values showed no significant differences between ONBs and SCCs, probably because both tumors can disrupt vascular endothelial cells and result in increased vascular permeability and leakage of the contrast agent.…”
Section: Discussionmentioning
confidence: 46%
“…Many studies have reported the correlation between DCEMRI perfusion parameters and the angiogenic factors in various cancers, but with variable results . Correlation of early enhancement and the washout kinetic curve with the breast tumor histologic grade and ER negativity have been reported .…”
Section: Mri‐related Methods In the Study Of Breast Cancer Metabolismmentioning
confidence: 99%